Ghosts! : the ultimate guide for ghost hunters - Brassey, Richard (London Orion Children's, 2006)
Britain is the ghost capital of the world and here are some of the very spookiest stories - the headless figure of Anne Boleyn arriving at her childhood home in a phantom coach, the marble statue that runs around brandishing a sword in a Devon church, the phantom Roman legionaries of York, and much more.
Include Color Illustrations
Keywords: Ghosts -- Haunted Places